A study on child labour as a form of child abuse in Malaysia - Nik Mahmod, Nik Ahmad Kamal; Che Mohd Salleh, Marhanum; Ali Mohamed, Ashgar Ali; Mohd, Azizah (2015)
International Labour Organization (ILO) estimates that there are about 250 million economically active children worldwide. In Malaysia, although the Children and Young Persons Act (Employment) 1966 prohibits the children to be employed, previous studies proved that there are high rate of working children in certain states in Malaysia. It is believed that thousands of working children in Malaysia to be in an environment which is potentially harmful to their physical, mental, emotional, and social development. To identify the types and instances of child abuse for the working children, a study has been conducted to 454 working children in four states in Malaysia. Based on data analysis, it is found that more than half (63%) of the working children have been emotionally abuse, 27% physically abused and at least 10% have been sexually abused. Majority of them are not happy with their current job and are regretful for not attending school. This represents their basic necessities to have proper education and they should not expose to work at this early age. This research contributes to increase the awareness of public and government to take care of the need of children basically on the issue of child abuse for working children.